2004
DOI: 10.1212/01.wnl.0000129990.32253.7b
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of donepezil in the treatment of neuropsychiatric symptoms in Alzheimer disease

Abstract: Donepezil has significant efficacy in the treatment of neuropsychiatric symptoms in patients with mild to moderate AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(183 citation statements)
references
References 20 publications
4
168
2
5
Order By: Relevance
“…Cholinesterase inhibitors and memantine have been reported to have small-to-medium effect size effects on neuropsychiatric symptoms, including psychosis and agitation; however, these data were obtained from secondary outcome measures and post hoc analyses of patients who often did not have clinically significant behavioral symptoms at baseline, and yet other trials have shown no effect of cognitive enhancers on behavior (Cummings et al, 2006a, b;Sink et al, 2005;McKeith et al, 2000;Trinh et al, 2003;Hermann et al, 2005). A prospective trial of donepezil for neuropsychiatric symptoms in outpatients with mildmoderate AD showed improvement in global neuropsychiatric symptoms during open-label treatment for 3 months, followed by symptomatic worsening only in placebo-treated patients during the subsequent randomized discontinuation phase of the trial (Holmes et al, 2004). Yet, these patients had relatively modest levels of behavioral symptoms.…”
Section: Other Psychotropicsmentioning
confidence: 99%
“…Cholinesterase inhibitors and memantine have been reported to have small-to-medium effect size effects on neuropsychiatric symptoms, including psychosis and agitation; however, these data were obtained from secondary outcome measures and post hoc analyses of patients who often did not have clinically significant behavioral symptoms at baseline, and yet other trials have shown no effect of cognitive enhancers on behavior (Cummings et al, 2006a, b;Sink et al, 2005;McKeith et al, 2000;Trinh et al, 2003;Hermann et al, 2005). A prospective trial of donepezil for neuropsychiatric symptoms in outpatients with mildmoderate AD showed improvement in global neuropsychiatric symptoms during open-label treatment for 3 months, followed by symptomatic worsening only in placebo-treated patients during the subsequent randomized discontinuation phase of the trial (Holmes et al, 2004). Yet, these patients had relatively modest levels of behavioral symptoms.…”
Section: Other Psychotropicsmentioning
confidence: 99%
“…In spite of this, the AChEIs may differ in their individual profiles, as the SPCs report agitation as a common AE (1-10%) with donepezil and rivastigmine treatment but rare with galantamine (0.01-0.1%) (Aricept SPC, 2007;Reminyl Tablets SPC, 2007;Exelon Capsules SPC, 2008). Furthermore, AChEIs have not consistently demonstrated a specific benefit on agitation in dementia (Gauthier et al, 2002;Holmes et al, 2004;Sink et al, 2005;Black et al, 2007;Howard et al, 2007).…”
Section: Agitationmentioning
confidence: 99%
“…One included trial 43 allowed the inclusion of patients with vascular dementia; however, the predominant disorder was AD and therefore the trial met the present review inclusion criteria (see Appendix 2). Eight published RCTs were parallel comparisons of donepezil with placebo, 41,[43][44][45][46][47][48][49] three RCTs compared two doses of donepezil with placebo, [50][51][52] one compared three doses of donepezil with placebo 53 and one was a crossover comparison of donepezil with placebo. 54 One unpublished RCT reports data on participants with mild AD.…”
Section: Donepezil Quantity and Quality Of Researchmentioning
confidence: 99%